Physiological effects of various light spectra on oxidative stress by starvation in olive flounder, Paralichthys olivaceus - Choi, Cheol Young; Choi, Ji Yong; Choi, Young Jae; Yoo, Jin-Hyung (Molecular & cellular toxicology, 2018)
Backgrounds The present study investigated the effects of different light wavelengths on starvation-induced oxidative stress and apoptosis in olive flounder, Paralichthys olivaceus , by using light-emitting diodes (LEDs; blue, green, and red) at two intensities (0.3 and 0.6 W/m 2 ) for 9 days. Methods We measured the expression and concentration of antioxidant enzymes, the levels of H 2 O 2 , lipid peroxidation (LPO), aspartate aminotransferase (AspAT), alanine aminotransferase (AlaAT) and apoptosis (levels of caspase-3) and DNA damage in olive flounder under experimental conditions. Results All parameters except the apaotosis parameter significantly increased by starvation and significantly decreased after exposure to green and blue light compared to white fluorescent light. Likewise, both caspase-3 and DNA damage increased due to starvation- induced oxidative stress, and green wavelength irradiation played a role in preventing this stress. Conclusion These results suggest that green and blue wavelengths can inhibit oxidative stress and apoptosis in starved olive flounder and that green light is particularly efficient for this. Furthermore, the irradiation of green wavelength can play a role in protecting against starvation stress.